Propargyl 4-[(18)F]fluorobenzoate: A Putatively More Stable Prosthetic group for the Fluorine-18 Labeling of Biomolecules via Click Chemistry - Vaidyanathan, Ganesan (2009)
Faster and more efficient approaches for radiolabeling biomolecules with short-lived (18)F are in dire need. Herein we report a new (18)F-labeled prosthetic group containing an acetylene function that permits the labeling of biomolecules via click chemistry. This template, propargyl 4-[(18)F]fluorobenzoate ([(18)F]PFB) was synthesized from a quaternary salt precursor in decay-corrected radiochemical yields of 58 ± 31%. Several model compounds containing an azide moiety—benzyl azide, two lysine derivatives and a transglutaminase-reactive peptide—were labeled using [(18)F]PFB via a click reaction in decay-corrected radiochemical yields of 88 ± 4%, 79 ± 33%, 75 ± 5%, and 37 ± 31%, respectively. Our results suggest that the novel agent [(18)F]PFB is a potentially useful template for the (18)F-labeling of biomolecules via click chemistry.